"La relación de la actividad física y la calidad de vida de los niños del quinto año de educación básica paralelo “B” de la unidad educativa “Luis Fernando Ruiz” - Valencia Tigse, Erika Ximena (2023)
The present investigation has the objective of strengthening physical activities for the improvement of the quality of life of children, in addition, each of these variants will be defined theoretically where it can be observed that there is a relationship between physical activity and quality of life, however, it is important to mention that in order to carry out this investigation it was necessary to apply the quantitative approach through the descriptive design, where five teachers and thirty-four students of the fifth year of General Basic Education of the Educational Unit "Luis Fernando Ruiz" participated, who were the main actors for the collection of the required information. As for the application of the technique, a questionnaire was established so that they can answer the questions, this through the survey instrument to identify issues related to the research, where the beneficiaries contributed with their participation by answering the survey, these results show that the surveyed population performs physical activities that allow them to stay healthy, allowing their lives to improve, through the development of body warming activities, thus contributing to the proper functioning of the body, finally a guide of physical activities will be delivered to be put into practice within the educational institution.